Engineered Resilient Systems with Value Focused Thinking. Issue 1 (July 2017) - Small, Colin; Parnell, Gregory; Pohl, Edward; Goerger, Simon R.; Cottam, Bobby; Specking, Eric; Wade, Zephan
Abstract: Complex DoD systems need to be resilient due to evolving adversarial and environmental threats. The DoD created a program called Engineered Resilient Systems (ERS) to increase resilience in future systems. In our ERS research, resilience has been separated into two parts, mission and platform resilience. Mission resilience is the ability of a system to repel, resist, absorb, and recover from environments and threats that occur on planned missions. Platform resilience is the ability of a system to adapt to new missions and new threats. Using capabilities based planning one can map platform and mission resilience. This paper addresses how a value‐focused thinking (VFT) multiple objective decision analysis (MODA) model is a useful tool for capabilities based assessments. If all performance objectives can be categorized as mission or platform resilience, this extra value above the threshold of the minimum performance can provide mission and platform resilience. Displaying this information in a value component chart and a floating value chart allows decision makers to consider resilience early in the acquisition decision making process.